ParentingWell: adapting a family-focused practice for parents with mental illness - Nicholson, Joanne; Heyman, Miriam; Escobar, Fernanda; Kaplan, Katharine (Frontiers in Psychiatry, 2025)
IntroductionThe ParentingWell Practice Approach is a family-focused practice approach for adults who are parents receiving mental health services. The ParentingWell Learning Collaborative (PWLC) was originally developed and tested within the Massachusetts behavioral health service system to prepare and support mental health practitioners in implementing ParentingWell. The purpose of the current study was to systematically adapt ParentingWell, including the PWLC, for further implementation and scaling-out in a new setting with a diverse target population, and address the following question: What are the essential considerations in adapting ParentingWell resources to a diverse, vulnerable, at-risk target population in an urban service delivery context?MethodsWe used a participatory approach, developmental evaluation design and mixed methods to document the adaptation process, and to assess preliminary acceptability, fit, and feasibility. The adaptation process included (1) establishment of an Adaptation Team consisting of a diverse and multi-disciplinary team of policy makers and practitioners; (2) review of ParentingWell content by community stakeholders; and (3) piloting of the PWLC model in the new context, with local agency personnel.ResultsThe Adaptation Team provided guidance related to enhancing the acceptability of ParentingWell and the PWLC, including considerations related to the training format and evaluation methods. Community stakeholders provided suggestions to strengthen the fit of ParentingWell resources, including the creation of plain language resources. Data from PWLC participants indicated that they benefitted from participation in the Learning Collaborative.DiscussionThis study provides preliminary evidence for the acceptability, fit, and feasibility of ParentingWell in an urban service context. Future research should include longitudinal data collection with both providers and parents to identify how providers use ParentingWell tools and strategies, and to evaluate the impact of ParentingWell on parents served and their children.